Catadores de materiais recicláveis: dimensões legislativas, ambientais e socioeconômicas diante da pandemia da covid-19 no munícipio de Toledo - PR - Zamuner, Angela (2022)
This research's main objective is to analyze the activities of recyclable material collectors, associated with ACATOL, on de grounds of Law nº 12.305/2010, considering the environmental and socioeconomic situation during the COVID-19 pandemic in the city of Toledo/PR. With the purpose of contextualizing the National Solid Waste Policy (Law nº 12.305/2010), twelve years after its enactment, especially regarding the reality of recyclable material collectors; in addition to identifying who is the collector of recyclable materials in the consumer society; and finally, to verify the situation of associations among recyclable material collectors and the situation imposed on them during the COVID-19 pandemic. The descriptive exploratory method was used for the theoretical fundation of the dissertation".The research has a quality-quantitative nature, as local and personal questions of the interviewees were observed, in addition to statistical data. It was found that the average age of recyclable material collectors associated with ACATOL is 52.25 years old; mostly women working with urban solid waste in Toledo/PR. The surveyed population was self-declared 50% black/brown and 50% non-black, with low education, fixed residence, and ignorance of the National Policy on Solid Waste. The non-use of personal protective equipment was one of the points of concern in this research, considering the frequent exposure to physical, chemical, and biological hazard. There were only six cases of COVID-19 in the research group, which reinforces the effectiveness of the vaccines, considering that they were obliged to receive doses of the vaccine. We admit the hypothesis that the vulnerability of the collector of recyclable materials was not totally changed with the institute of the National Policy on Solid Waste. And that we still need public policies, with an emphasis on education and health to improve the quality of life of these people. The selective collection in the municipality of Toledo – PR was not stopped during the pandemic, considering the measures indicated and made public, we verified that despite the low incidence of cases of COVID-19, there is an intrinsic risk that should be managed.